Effect of Corporate Social Responsibility Disclosure and Capital Structure on Company Value with Profitability as a Moderating Variable - A. Riska Amelia Idris; Fahrina Mustafa (SAFE-Network, 2026)
This study aims to analyze the influence of Corporate Social Responsibility and capital structure on firm value, with profitability as a moderating variable, in companies in the Property and Real Estate subsector listed on the Indonesia Stock Exchange for the 2019–2023 period. This study employed a quantitative approach with secondary data obtained from company financial reports. Purposive sampling was used to select 16 companies with a total of 75 observations after removing outliers. Data analysis was performed using multiple linear regression and Moderated Regression Analysis using SPSS. The results indicate that CSR has a negative and significant effect on firm value, while capital structure has a positive and significant effect. Furthermore, profitability has been shown to strengthen the influence of CSR on firm value, but it cannot moderate the effect of capital structure on firm value. The findings of this study indicate that investors still view CSR activities as a cost burden if not balanced by a high level of profitability. Meanwhile, an optimal capital structure can increase firm value because it provides investors with confidence in the company's ability to manage funding sources effectively.